The Effect of Interval Training on Cardiovascular Endurance and Agility of Students in Futsal Extracurricular SMK Negeri 1 Trenggalek - Muhammad Soleh Fudin; Mohammad Faizza Hafidz Izzul Fikri; Nendra Febrianto; Sugeng Sulendro (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
Background of study: Interval training is a form of physical activity that involves alternating periods of high and low intensity training to improve speed, strength, and endurance. The primary challenge for most futsal players is their physical condition, particularly cardiovascular endurance and agility. This study aims to determine the effect of interval training on cardiovascular endurance and agility, as well as the relationship between endurance and agility. The scope of this study is the futsal extracurricular activity at State Vocational High School 1 Trenggalek. Methods: This research employed a quantitative and experimental method with a one-group pretest-posttest design. The sample consisted of 20 students, using a purposive sampling technique. Data collection for cardiovascular endurance was conducted using a multistage fitness test, and data collection for agility using a zigzag run test. Data analysis used inferential statistics. Result: The results of this study indicate the effect of interval training on students' cardiovascular endurance and agility, as evidenced by the significant difference in students' cardiovascular endurance and agility before and after training, which is reinforced by a p value of 0.000 < 0.05. In addition, it also shows the influence of cardiovascular endurance on students' agility with a p value of 0.000 < 0.005. Conclusion: This study concludes that interval training can be used to improve cardiovascular endurance and agility in futsal. Furthermore, the better the cardiovascular endurance, the more positive the impact on agility.